Effectiveness of educational intervention and cognitive rehearsal on perceived incivility among emergency nurses: a randomized controlled trial - Shohreh Kousha; Ali Shahrami; Mohammad Mehdi Forouzanfar; Neda Sanaie; Foroozan Atashzadeh-Shoorideh; Victoria Skerrett (BMC, 2022)
Abstract Background Witnessing or experiencing of incivility affected the nurses' perception of the ethical climate and quality of their work life. The aim of this study was to investigate the effectiveness of educational intervention and cognitive rehearsal on perceived incivility among emergency nurses. Method This study was conducted as a randomized controlled parallel group clinical trial. Eighty emergency nurses participated in this study and were randomly assigned to intervention and control groups during December 2019-March 2020. Cognitive rehearsal program (include of definitions of incivility, ten common incivilities and appropriate practice methods for responding to each and role-plays) was delivered in five two-hour sessions over three weeks on different working days and shifts. The control group received only written information about what incivility is and how to deal with it before the implementation of intervention and one month after the completion of the training sessions, the demographic information form and the incivility scale were completed by the nurses. Results The results showed that there was a significant effect on overall incivility, general incivility, and supervisor incivility between the intervention and control groups. However, these significant reductions were seen in control group who received only written education. There were no significant differences in nurse's incivility towards other nurses, physician incivility, and patient/visitor incivility between the two groups. Conclusion The cognitive rehearsal program did not decrease perceived incivility among emergency department nurses in the short term. Trial registration Our research was registered on clinicaltrials.gov. Registration number: IRCT20200714048104N1 , first registration 16/07/2020.